2017
DOI: 10.33158/asb.2017v3i2p113
|View full text |Cite
|
Sign up to set email alerts
|

Substrates and IBA concentrations on rooting of herbaceous cuttings of blueberry ‘Woodard’

Abstract: Brazil offers great perspectives for the expansion of blueberry (Vaccinium spp.) cultivation areas, mainly in family agriculture areas. Among the factors that limit the expansion of this culture is the difficulty to propagate some cultivars. Thus, the objective of this work was to evaluate the use of different substrates and concentrations of indolebutyric acid (IBA) for blueberry cuttings cvs. Woodard rooting, to optimize seedlings production system. The experimental design was totally randomized in a 3X3 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Fisher et al ( 2016) also reported that when foliar nutrients had been applied, there was an increase in rooting, as the substrate used was inert and the rooting period was relatively long. The length of the longest root in cuttings collected in autumn is in agreement with those found by Yamamoto et al (2017), who observed from means from 3.5 cm to 7.1 cm. However, the means obtained in the summer were higher than that recorded by Nascimento et al (2011), 3.79 cm.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Fisher et al ( 2016) also reported that when foliar nutrients had been applied, there was an increase in rooting, as the substrate used was inert and the rooting period was relatively long. The length of the longest root in cuttings collected in autumn is in agreement with those found by Yamamoto et al (2017), who observed from means from 3.5 cm to 7.1 cm. However, the means obtained in the summer were higher than that recorded by Nascimento et al (2011), 3.79 cm.…”
Section: Resultssupporting
confidence: 92%
“…There are reports of high rooting percentage of 'Woodard' blueberry cuttings collected during the growing season, reaching means of 80.0% and 82.5% in summer, mainly when multiplicated by minicuttings (KOYAMA et al, 2018;NASCIMENTO et al, 2011). On the other hand, when cuttings are collected in autumn and winter, the percentage of rooting is reduced, ranging from 29.5% to 66.7% (FISCHER et al, 2008;KOYAMA et al, 2018;SHAHAB et al, 2018;SHAHAB et al, al., 2018;YAMAMOTO et al, 2017). Thus, it is preferable that the collection of 'Woodard' herbaceous cuttings be carried out in the summer.…”
Section: Resultsmentioning
confidence: 99%
“…Among the vegetative propagation processes, minicutting is an improvement of cutting technique and has been used in the multiplication of several plant species, such as eucalyptus (Eucalyptus benthamii) (Brondani, Baccarin, Ondas, Gonçalves, & Almeida, 2012), Australian cedar (Toona ciliata) (Silva, Barroso, Souza, Ferreira, & Carneiro, 2012), and also in several fruit trees, such as guava tree (Psidium guajava) (Marinho, Milhem, Altoé, Barroso, & Pommer, 2009;Altoé & Marinho, 2012), araçá (Psidium cattleianum) (Altoé, Marinho, Terra, & Barroso, 2011), soursop (Annona muricata) (Figueirêdo, Vilasboas, Oliveira, Sodré, & Sacramento, 2013), blueberry tree (Vaccinium spp.) (Fischer, Fachinello, Antunes, Fischer, & Giacobbo, 2013;Yamamoto et al, 2017;Koyama et al, 2018), peach tree (Prunus persica) (Timm, Schuch, Tomaz & Mayer, 2015a;Tomaz, Schuch, Peil, & Timm, 2014;Tomaz, Schuch, Peil, & Pereira, 2016;Ramm, Schuch, Fagundes, Silva, & Moreira, 2017), cherry (Ozelame, Affonso, Cappellaro, Schuch, &Tomaz, 2018, blackberry andraspberry (Sommer et al, 2016;Fagundes et al, 2016), and more recently the olive tree (Olea europaea) (Casarin, Moreira, Raasch, Timm, & Schuch, 2018;Moreira & Schuch, 2018).…”
Section: Introductionmentioning
confidence: 99%